1993
DOI: 10.1002/ca.980060302
|View full text |Cite
|
Sign up to set email alerts
|

Insertion orientation of terminal vastus lateralis obliquus and vastus medialis obliquus muscle fibers in human knees

Abstract: The quadriceps mechanism consists of the patellar ligament distally and the quadriceps tendon proximally. The quadriceps tendon is the confluence of the tendinous portions of the vastus medialis, vastus lateralis, vastus intermedius, and rectus femoris. Lieb and Perry (J. Bone Joint Surg. 5OA:1535-1547, 1968) have described the vastus medialis obliquus (VMO) and Hallisey et al. (J. Bone Joint Surg. 694.545549, 1987) have described the vastus lateralis obliquus (VLO). These muscles are the terminal medial and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 14 publications
0
16
1
1
Order By: Relevance
“…In comparison, the pennation angle reported by Hallisey et al (1987), Bennett et al (1993) and Weinstabl et al (1989) showed a clear trend towards a more obliquely directed fascicular orientation in the distal part of the VL muscle. Hallisey et al (1987) determined the pennation angle in 41 cadaveric knees and reported a mean value of 48.58 and 38.68 for the pennation angle of VLO in male and female specimens, respectively.…”
Section: Muscle Architecturementioning
confidence: 64%
See 3 more Smart Citations
“…In comparison, the pennation angle reported by Hallisey et al (1987), Bennett et al (1993) and Weinstabl et al (1989) showed a clear trend towards a more obliquely directed fascicular orientation in the distal part of the VL muscle. Hallisey et al (1987) determined the pennation angle in 41 cadaveric knees and reported a mean value of 48.58 and 38.68 for the pennation angle of VLO in male and female specimens, respectively.…”
Section: Muscle Architecturementioning
confidence: 64%
“…In eight anatomical studies, the pennation angle of VL was investigated, providing a wide range of reported values (Lieb and Perry, 1968;Reider et al, 1981;Wickiewicz et al, 1983;Hallisey et al, 1987;Weinstabl et al, 1989;Friederich and Brand, 1990;Bennett et al, 1993;Andrikoula et al, 2006). Reider et al (1981) stated that fascicles of VL approached the patella at a mean angle of 318 (range 228-458), similar to that reported by Andrikoula et al (2006).…”
Section: Muscle Architecturementioning
confidence: 73%
See 2 more Smart Citations
“…However, this previous researches evaluating the patellofemoral pain syndrome has not included the oblique portion of the vastus lateralis muscle, which is separated from the longus component by fascial planes and has different functions 10,11 . The most oblique portions of vastus medialis and of vastus lateralis, would be the portions most prepared anatomically to control the position of the patella with respect to the trochlear surface of the femur 7 , play an important function in patellar orientation within the femoral trochlea 10 and would be responsible for the control and stability of the patella 7 .…”
Section: Atividade Do Vasto Lateral Oblíquo Na Marcha De Sujeitos Commentioning
confidence: 99%